Unlimited understanding - Rehm, Georg; Uszkoreit, Hans (Infotheca - Journal for Digital Humanities; Vol 14 No 1 (2013): Infotheca - Journal of Informatics and Librarianship, 2024)
Europe is facing a severe communication crisis. META-NET’s recent study “Europe’s Languages in the Digital Age,” published last year in 31 volumes for 31 languages, shows that most European languages are threatened with “digital extinction”: they are not sufficiently supported by information technology to survive in a digital world. Our immense linguistic diversity is a defining part of our continent’s cultural heritage, but at the same time it is also an obstacle to commerce, trade, and further European integration.